2020
DOI: 10.1111/bcpt.13393
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposures to e‐cigarettes and heat‐not‐burn products reported to the Czech Toxicological Information Centre over a 7‐year period (2012‐2018)

Abstract: E‐cigarettes and heat‐not‐burn cigarettes (HNBC) present new health risks due to their rising popularity, high content of nicotine and serious adverse effects. The objective of the study was to analyse the cases of acute exposure to e‐cigarettes, e‐liquids and HNBC products containing nicotine that led to toxicological consultations at our poisons control centre during a 7‐year period (2012‐2018) and identify the categories of special concern that require further investigation and intervention. The demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…There is limited research on the association between HTP use, exposure to toxic constituents, and suicidality. A recent study found that HTPs might be used as a tool for suicide attempts 26 .…”
Section: Introductionmentioning
confidence: 99%
“…There is limited research on the association between HTP use, exposure to toxic constituents, and suicidality. A recent study found that HTPs might be used as a tool for suicide attempts 26 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Surprisingly, acute intoxication attributed to nicotine overdose related to these products has been reported. 5 Generally, highly concentrated liquid nicotine or "e-liquid" that e-cigarettes aerosolize is much more hazardous because of its quick absorption. 1 However, ingestion of large amounts of HNB cigarettes can also be life-threatening because they contain as much nicotine as regular tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, intake of 40 to 60 mg of oral nicotine or 5 cigarettes has been shown to be lethal; however, the actual lethal dose is implied to be much greater based on previous reports showing that the majority of patients who were potentially harmed were asymptomatic or presented with only mild symptoms. 5 Possible explanations include decrease of actual intake as a result of vomiting, difference in absorption rates between cigarette sticks and nicotine liquid, and the rapid metabolism of nicotine in the liver. 1,9 Nevertheless, the present case could have been fatal given a previously reported case of lethal acute nicotine intoxication attributed to the intentional ingestion of 9 regular cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obecně samozřejmě nelze žádný nikotinový výrobek doporučovat nekuřákům včetně dětí. Zejména u nich může dojít k intoxikaci nikotinem při vypití tekutiny EC, u nás se jedná ročně řádově o desítky telefonátů (dotazů) na Toxikologické informační středisko (11).…”
Section: Harm Reduction -Nikotin S Nižším Rizikemunclassified